CircAMOTL1 Promotes Tumorigenesis Through miR-526b/SIK2 Axis in Cervical Cancer - Sun, Zhengwei; Niu, Sanqiang; Xu, Fuxia; Zhao, Weidong; Ma, Rong; Chen, Mingwei (Frontiers in Cell and Developmental Biology, 2020)
Background: Cervical cancer is one of the most common malignancies in women, leading to major health problems due to high morbidity and mortality. Numerous studies have demonstrated that circRNAs could be participated in the progression of multifarious diseases, especially plentiful carcinomas. CircAMOTL1 (angiomotin-like1, ID: hsa_circ_0004214), which is located on human chromosome 11:9 4532555-94533477, is involved in the occurrence of breast cancer etc. However, the intrinsic and concrete molecular mechanism of circAMOTL1 in cervical carcinomas remained thoroughly unclear, which was also the bottleneck of circRNA studies in cancer. Methods: The relative circAMOTL1 and miR-526b-5p expression levels in 85 cervical carcinoma patients’ specimens and multifarious cervical cancer carcinoma cell lines were detected by RT-qPCR. Through experiments such as loss-function and overexpression, the biological effects of circAMOTL1 and miR-526b-5p on cervical carcinomas the proliferation, migration, apoptosis and tumorigenicity etc. were explored. Dual luciferase reporter gene analysis, western blot and other methods were used to explore the circAMOTL1 potential mechanism in cervical carcinomas. Results: In our experiments, our researches showed that circAMOTL1 was significantly higher expression in cervical carcinomas specimens and cell lines. Further experiments showed that knockdown of circAMOTL1 could restrain the malignant phenotype ，AKT signaling and epithelial-mesenchymal transition (EMT) of in cervical carcinomas cells, meanwhile miR-526b-5p was in contrast and miR-526b-5p could partially reverse circAMOTL1 malignant cervical tumor cell function. CircAMOTL1 acts as a microRNA sponge that actively regulates the expression of SIK2 (salt-inducible kinase 2) to sponge miR-526b-5p and subsequently increases malignant phenotypes of cervical carcinomas cells, and circAMOTL1 performs a carcinogenic effect and miR-526b-5p as the opposite function of antioncogene in the cervical carcinomas’ pathogenesis. Conclusion: CircAMOTL1-miR-526b-5p-SIK2 axis is referred to the malignant progression and development of cervical carcinomas. CircAMOTL1 expression was inversely correlated with miR-526b-5p and positively correlated with SIK2 mRNA in cervical cancer tissues. Thus, circAMOTL1 exerted an oncogenic role in cervical cancer progression through sponging miR-526b-5p. Taken together, our study reveals that circAMOTL1 acted as oncogene and may be a potential therapeutic target in cervical cancer.